I am right, you are wrong: how biased assimilation increases the perceived gap between believers and skeptics of violent video game effects. - Tobias Greitemeyer (PLoS ONE)
Background Despite hundreds of studies, there is continuing debate about the extent to which violent video games increase aggression. Believers argue that playing violent video games increases aggression, but this stance is disputed by skeptics. The present study addressed believers' and skeptics' responses to summaries of scientific studies that do or do not present evidence for increased aggression after violent video game play. Methods/principal findings Participants (N = 662) indicated whether they believed that violent video games increase aggression. Afterwards, they evaluated two opposing summaries of fictitious studies on the effects of violent video play. They also reported whether their initial belief had changed after reading the two summaries and indicated again whether they believed that violent video games increase aggression. Results showed that believers evaluated the study showing an effect more favorably than a study showing no effect, whereas the opposite was observed for skeptics. Moreover, both believers and skeptics reported to become more convinced of their initial view. In contrast, for actual attitude change, a depolarization effect was found. Conclusions/significance These results suggest that biased assimilation of new information leads believers and skeptics to become more rather than less certain of their views. Hence, even when confronted with mixed and inconclusive evidence, the perceived gap between both sides of the argument increases.